Uno strano modo di pregare. I passalorinchiti alle origini dell'esicasmo ? - Nardi, Carlo (Augustinianum, 2011)
Important issues of Sinaitic and Byzantine hesychasm suggest the hypothesis of ancient derivations from the movement of the Passalorynchites or the Tascodrugites, which has connections with the Montanist world. This religious experience, still alive in the fourth century, had peculiar modalities of prayer connected with breathing discipline, similar to respiration techniques present in hesychasm during the first centuries of second millennium. The article emphasizes spiritual ways that demonstrate an underground continuity between ancient uses and noteworthy aspects of Byzantine monasticism and its developments, especially in Slavic traditions.